Logic model evaluation and the analysis of job motivation for pre-paring the performance indicators of government institution: case of Klungkung, Bali - Made Aristia Prayudi; Gusti Ayu Ketut Rencana Sari Dewi; Putu Riesty Masdiantini (Universitas Hayam Wuruk Perbanas, 2020)
When compared to other districts in Bali Province, Klungkung has the lowest performance accountability score. The current study aims to evaluate the technical and psychological aspects of performance indicators development process of the local government. The technical aspect evaluation was done by implementing logic model analysis procedures and adopting a four-quadrant analysis approach. The Â psychological aspect analysis was conducted by examining the motivational factors taken from the perspective of Institutional Theory for determining individual behavior in developing performance indicators in governmental organizations. The results show that there is a discrepancy in the number of performance indicators presented in the planning and performance reporting documents, as well as an absence of logical relationships among them. Psychologically, the quality of Klungkungâ€™s performance indicators development is determined by the perception of the performance indicators matrix difficulty, the perceived usefulness of technical training, the level of top management commitment, the assertiveness enforcement of the regulations, and the existence of social pressure and pressure on professionalism. It can be implied that technical policies need to be formulated by local government organizations. Â